Experimental verification of railway substructure with application of reinforced geocomposite - Izvolt, Libor; Mecar, Martin (Communications - Scientific letters of the University of Zilina, 2004)
In the paper the authors present results of experimental measurements realized in a testing stand which was built for evaluation of reinforced effect of geocomposite MACRIT GTV/50-50 B applied into a railway substructure. Methodology of experimental measurements, observed physical characteristics of used grounds and results of static loading tests for various granularity and thickness of subbase material (150 mm –600 mm) are described. The main result of the experimental evaluation of two-tested subbase materials is a proposal of nomograms for dimensioning the railway substructure with application of topical geosynthetic material.